RESILIENSI AKADEMIK SISWA PONDOK PESANTREN - Jalal, Novita Maulidya (JCI Publisher, 2025)
This study aims to examine the academic resilience of Islamic boarding school students through a library research approach by reviewing national and international literature related to personal, social, spiritual, and pedagogical factors that shape students’ academic endurance. Findings indicate that academic resilience among santri develops through the interaction of self-efficacy, intrinsic motivation, self-regulation skills, and social support from peers, teachers, and dormitory caregivers. The disciplined, communal, and religious environment of pesantren strengthens adaptive coping mechanisms, particularly in managing academic pressure, demanding study schedules, and religious obligations. International literature highlights that interpersonal support and religious culture enhance students’ psychological resilience and academic engagement. Moreover, spiritual routines such as prayer and scriptural study function as emotional regulation tools that promote mental stability. The review also reveals that pesantren’s intensive instructional methods foster long-term academic perseverance, although they may increase stress when not accompanied by adequate social support. Overall, this study underscores that academic resilience among santri is a product of the holistic ecology of Islamic boarding school education. Therefore, strengthening resilience requires integrated strategies that simultaneously develop psychological, social, and spiritual capacities. Keywords : Academic Resilience, Islamic Boarding School,Students